Capital Taxation under Political Constraints - Scheuer, Florian; Wolitzky, Alexander (American Economic Review, 2016)
This paper studies optimal dynamic tax policy under the threat of political reform. A policy will be reformed ex post if a large enough coalition of citizens supports reform; thus, sustainable policies are those that will continue to attract enough political support in the future. We find that optimal marginal capital taxes are either progressive or U-shaped, so that savings are subsidized for the poor and/or the middle class but are taxed for the rich. U-shaped capital taxes always emerge when individuals' political behavior is purely determined by economic motives. (JEL D12, D14, D31, D72, H21, H25)